Vertical heterostructures for symmetrical and reversible solid oxide fuel cells - Zamudio-García, Javier; Chiabrera, Francesco; Losilla, Enrique R.; Marrero-López, David; Esposito, Vincenzo (Elsevier, 2024)
Interfacial modification using functional metal oxides holds great potential for enhancing the electrochemical performance of solid oxide fuel cells (SOFCs). This study presents a redox-stable vertically aligned nanostructure (VAN) thin film based on a heteroepitaxial perovskite-fluorite nanocomposite prepared by pulsed laser deposition on different substrates. The self-assembled functional layers consist of alternating columns of two well-differentiated phases, (La0.8Sr0.2)0.95Fe0.8Ti0.2O3−δ-Ce0.9Gd0.1O1.95 (LSFT-CGO) VAN, with multiple strained vertical interfaces. The coexistence of two immiscible phases at the nanoscale significantly extends the triple phase boundary (TPB) and reaction sites, resulting in fast electrochemical redox reactions. The LSFT-CGO VAN active layer demonstrates improved performance under both air and H2 conditions, with polarization resistances of 2.9 and 75.9 Ω cm2 at 650 °C, respectively. The nanoengineering design of functional metal oxides featuring hierarchical columnar architecture represents a significant step towards developing efficient energy conversion devices, particularly symmetrical and reversible SOFCs.
PID2021-126009OB-I00 funded by MCIN/AEI/10.13039/501100011033 TED2021-129836B-I00, funded by MCIN/AEI/10.13039/501100011033 (Grants No. 9041-00034B and 1032-00261B) funded by DFF
Keywords: Pilas de combustible; Electroquímica; VAN; Solid oxide fuel cells; Ceria; Ferrite; Thin films; Functional metal oxides